Economic evaluation of Mumbai and its satellite cancer registries: Implications for expansion of data collection. (December 2016) - Koyande, Shravani; Subramanian, Sujha; Edwards, Patrick; Hoover, Sonja; Deshmane, Vinay; Tankga, Florence; Dikshit, Rajesh; Saraiya, Mona
Highlights: Cost data was collected from Mumbai and three satellite registries for one year. Most registry resources were allocated to labor. The cost per case registered was a little less than 4 (year 2014 USD). Centralization of activities likely resulted in efficient operations. Abstract: Background: The Mumbai Cancer Registry is a population-based cancer registry that has been in operation for more than five decades and has successfully initiated and integrated three satellite registries in Pune, Nagpur, and Aurangabad, each covering specific urban populations of the Indian state Maharashtra. Data collectors at the satellites perform data abstraction, but Mumbai carries out all other core registration activities such as data analysis and quality assurance. Each of the three satellite registries follows the same data collection methodology as the main Mumbai Cancer Registry. This study examines the cost of operating the Mumbai and its satellite cancer registries. Methods: We modified and used the Centers for Disease Control and Prevention's (CDC's) International Registry Costing Tool ( IntRegCosting Tool ) to collect cost and resource use data for the Mumbai Cancer Registry and three satellites. Results: Almost 60% of the registration expenditure was borne by the Indian Cancer Society, which hosts the Mumbai Cancer Registry, and more than half of the registry expenditure was related to data collection activities. Across the combined registries, 93% of the expenditure was spent on labor. Overall, registration activities had a low cost per case of 226.10 Indian rupees (or a little less than 4.00 US dollars in 2014 [used average exchange rate in 2014: 1 US = 60 Indian rupees]). Conclusion: The centralization of fixed-cost activities in Mumbai likely resulted in economies of scale in operating the Mumbai and satellite registries, which, together, report on almost 20, 000 cancer cases annually. In middle-income countries like India, where financial resources are limited, the operational framework provided by the Mumbai and satellite registries can serve as a model for other registries looking to expand data collection.